2018
DOI: 10.1038/s41467-018-03685-z
|View full text |Cite
|
Sign up to set email alerts
|

The world’s largest High Arctic lake responds rapidly to climate warming

Abstract: Using a whole-watershed approach and a combination of historical, contemporary, modeled and paleolimnological datasets, we show that the High Arctic’s largest lake by volume (Lake Hazen) has succumbed to climate warming with only a ~1 °C relative increase in summer air temperatures. This warming deepened the soil active layer and triggered large mass losses from the watershed’s glaciers, resulting in a ~10 times increase in delivery of glacial meltwaters, sediment, organic carbon and legacy contaminants to Lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
146
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(152 citation statements)
references
References 41 publications
6
146
0
Order By: Relevance
“…High-latitude lakes, especially those with perennial ice covers, are extremely sensitive to climate variability, particularly with regard to the dynamics of their ice covers. Owing to this sensitivity, ice thickness changes have been closely documented over the past several decades in both Arctic and Antarctic lakes (Adrian et al, 2009;Doran, Priscu, et al, 2002;Lehnherr et al, 2018;Mueller et al, 2009;Obryk, Doran, Friedlaender, et al, 2016;Obryk, Doran, Hicks, et al, 2016;Paquette et al, 2014;Vincent et al, 2008;Vincent et al, 1998;Wharton et al, 1989). For example, the ice-free area of a deep high-latitude Arctic Lake Hazen increased by 3 km 2 /year over the last two decades in response to surface air temperature warming of only~1°C (Lehnherr et al, 2018), and shallow (<3 m deep) Alaskan lakes transitioned from winter grounded ice to floating ice as a direct response to increased surface air temperatures (Surdu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-latitude lakes, especially those with perennial ice covers, are extremely sensitive to climate variability, particularly with regard to the dynamics of their ice covers. Owing to this sensitivity, ice thickness changes have been closely documented over the past several decades in both Arctic and Antarctic lakes (Adrian et al, 2009;Doran, Priscu, et al, 2002;Lehnherr et al, 2018;Mueller et al, 2009;Obryk, Doran, Friedlaender, et al, 2016;Obryk, Doran, Hicks, et al, 2016;Paquette et al, 2014;Vincent et al, 2008;Vincent et al, 1998;Wharton et al, 1989). For example, the ice-free area of a deep high-latitude Arctic Lake Hazen increased by 3 km 2 /year over the last two decades in response to surface air temperature warming of only~1°C (Lehnherr et al, 2018), and shallow (<3 m deep) Alaskan lakes transitioned from winter grounded ice to floating ice as a direct response to increased surface air temperatures (Surdu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this sensitivity, ice thickness changes have been closely documented over the past several decades in both Arctic and Antarctic lakes (Adrian et al, 2009;Doran, Priscu, et al, 2002;Lehnherr et al, 2018;Mueller et al, 2009;Obryk, Doran, Friedlaender, et al, 2016;Obryk, Doran, Hicks, et al, 2016;Paquette et al, 2014;Vincent et al, 2008;Vincent et al, 1998;Wharton et al, 1989). For example, the ice-free area of a deep high-latitude Arctic Lake Hazen increased by 3 km 2 /year over the last two decades in response to surface air temperature warming of only~1°C (Lehnherr et al, 2018), and shallow (<3 m deep) Alaskan lakes transitioned from winter grounded ice to floating ice as a direct response to increased surface air temperatures (Surdu et al, 2014). A shift from perennial to seasonal ice covers in the Arctic lakes showed that the transition is abrupt, rather than a gradual process (Mueller et al, 2009;Paquette et al, 2014), and results in a cascading ecological shift in the water column owing to wind-driven mixing and higher heat transfer (Lehnherr et al, 2018;Mueller et al, 2009;Vincent et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although some models predict that small temperature increases (<2.5°C), may increase Arctic charr growth rates (Budy & Luecke, ; Elliott & Elliott, ; Reist et al, ), Lehnherr et al. () have attributed a rapid decline in physiological condition of Arctic charr in Lake Hazen on Ellesmere Island to climate change. Furthermore, studies indicate that the eggs of the Arctic charr are not expected to survive a freshwater temperature increase of 5°C, and temperatures exceeding 22–23°C will likely result in mass adult mortality unless cold water refugia are present (Elliott & Elliott, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Arctic charr may provide a useful model to study the impact of climate change on cold water adapted fish species and Arctic freshwater ecosystems in general. Although some models predict that small temperature increases (<2.5°C), may increase Arctic charr growth rates (Budy & Luecke, 2014;Elliott & Elliott, 2010;Reist et al, 2006a), Lehnherr et al. (2018) have attributed a rapid decline in physiological condition of Arctic charr in Lake Hazen on Ellesmere Island to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is transforming Arctic ecosystems: elevated temperatures and increasing precipitation 37 have facilitated permafrost thaw (Romanovsky et al, 2010) and glacial melt (Lehnherr et al, 2018;38 Milner et al, 2017), leading to impacts on the functioning of aquatic and terrestrial ecosystems, and the 39 natural services they provide. Microbes are major players in the biogeochemical cycling of organic 40 matter and inorganic nutrients; as such studying contemporary Arctic microbial communities is critical 41 for both documenting and predicting how these cycles might respond to ongoing and future 42 environmental change.…”
Section: Introduction 36mentioning
confidence: 99%